Teaching competency ... Is it possible? (Journal of Parents and Teachers, 2013)
In this article, the author explains the way to teach competences through his own experience in the classroom. He makes a proposal based on his research about problem-based-learning, describing a methodology (presentation, development and evaluation) and some application ideas.
Keywords: Problem-based learning; Competences; Cooperative learning; Activities